2020
DOI: 10.1155/2020/7054315
|View full text |Cite
|
Sign up to set email alerts
|

Two Pathogenic Gene Mutations Identified Associating with Congenital Cataract and Iris Coloboma Respectively in a Chinese Family

Abstract: Purpose. To screen out pathogenic genes in a Chinese family with congenital cataract and iris coloboma. Material and Methods. A three-generation family with congenital cataract and iris coloboma from a Han ethnicity was recruited. DNA was extracted from peripheral blood samples collected from all individuals in the family. Whole exon sequencing was employed for screening the disease-causing gene mutations in the proband, and Sanger sequencing was used for other members of the family and a control group of 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Wolframin variants are reported to result in ER stress and loss of ER function, disrupting the export of vesicle cargo proteins such as insulin. 17 To date four autosomal dominant families (including one in this study) and three sporadic cases have been documented with variants in WFS1 causing isolated cataracts or other WS pathologies [18][19][20][21] (table 3). The majority of recessive WFS1 inactivating variants cause typical WS, whereas dominant non-inactivating variants are associated with less severe, but more varied, phenotypes.…”
Section: Discussionmentioning
confidence: 87%
“…Wolframin variants are reported to result in ER stress and loss of ER function, disrupting the export of vesicle cargo proteins such as insulin. 17 To date four autosomal dominant families (including one in this study) and three sporadic cases have been documented with variants in WFS1 causing isolated cataracts or other WS pathologies [18][19][20][21] (table 3). The majority of recessive WFS1 inactivating variants cause typical WS, whereas dominant non-inactivating variants are associated with less severe, but more varied, phenotypes.…”
Section: Discussionmentioning
confidence: 87%
“…Boatz et al found that P24T variants aggregated under in vivo conditions with a native-like fold by a non-amyloid mechanism, which was considered to be the surfacemediated changes in protein-protein interactions [39]. Li et al revealed that P24T mutant changed a pyrrole ring of the wild type into a hydrophilic structure, affecting the correct folding of the protein [35].…”
Section: Discussionmentioning
confidence: 99%
“…Boatz et al found that p.P24T variant aggregated under in vivo conditions with a native-like fold by a non-amyloid mechanism, which was considered to be the surface-mediated changes in protein–protein interactions [ 18 ]. Li et al revealed that p.P24T mutant changed a pyrrole ring of the wild type into a hydrophilic structure, affecting the correct folding of the protein [ 19 ]. The findings presumed that the p.P24T might initiate aggregation or polymerization and result in the formation of CC.…”
Section: Discussionmentioning
confidence: 99%
“…p.P24T was also found to be responsible for several different phenotypes of CC except for coralliform cataract, e.g., lamellar cataract, cerulean cataract, the fasciculi form cataract and total cataract [ 9 – 14 , 19 , 24 , 26 39 ]. Although there was variability in cataract phenotypes among the p.P24T-bearing families, coralliform cataract was the most common phenotype, and more importantly, all Chinese families including our ten families were involved coralliform cataract.…”
Section: Discussionmentioning
confidence: 99%